Leading Attraction to “Visit of East Kalimantan”. Prospects of Pampang Cultural Village, Samarinda - ZA, Saida Zainurossalamia; TRICAHYADINATA, Irsan; HUDAYAH, Syarifah; MUSTARI, Aprilya (Journal of Environmental Management and Tourism; Vol 12 No 8 (2021): JEMT, Volume XII, Issue 8(56), Winter 2021, 2021)
A region needs to promote the attributes of tourism: to be an attraction for tourists and a special symbol so that they easily recognized it. This study seeks to learn about the attributes of tourism products, location, and electronic word of mouth (e-WoM) on consumer decisions. The study focused on those visiting the Pampang Cultural Village in Samarinda City (Indonesia). We concentrate the limitation of the variables on the independent variables (tourism product attributes, location, and e-WoM). Meanwhile, the dependent variable is the visiting decisions. The questionnaire became a research instrument that was distributed to 75 respondents, of whom were visitors in the Pampang Cultural Village. Quantitative methods refer to interpreting survey data through the IBM Statistical Product and Service Solution (SPSS) system version 25. Identification based on the results of the interview presented that the tourism product attributes, location, and e-WoM as a whole had a positive and significant effect on visiting decisions. The Government of East Kalimantan Province has so far labeled “Visit East Kalimantan” as part of the national tourism program, and it is growing booming. Future studies need to pay attention to the sample size, the development of the variables, and the methods applied so that there will be new and more varied findings.